The Influence of Service Quality Level and Price on JNE Customer Satisfaction Bandung City Branch Express - Jimmy Maming; Heliani; Andri Ardhiyansyah (The Es Economics and Entrepreneurship, 2022)
When customers are satisfied, harmonious relations between producers and buyers are established, a good basis for repeat purchases is formed, and recommendations are formed by word of mouth, which benefits the company. Customers enjoying service can be seen as a situation where the expectations of service consumers are following those obtained from the services provided to consumers. Customers will be disappointed if the company's services do not meet their expectations. This writing uses a quantitative research approach. The focus of this research is the influence of the level of service quality and price on customer satisfaction. The location of this research was conducted at JNE Express Bandung City Branch. Based on the discussion, 1) service quality has a positive and significant effect on customer satisfaction; 2) price has a positive and significant effect on customer satisfaction, and 3) service quality and price have a simultaneous effect on customer satisfaction. As for suggestions and recommendations to related parties, JNE Express at JNE Express Bandung City Branch is expected to be able to improve service quality and prices to increase customer satisfaction.